E-Evaluasi Berbasis Google Form dan Quizizz - Tiara Riski, Yunia; Nur Huda, Muhammad (AIJER: Algazali International Journal Of Educational Research, 2024)
Nowadays, teaching and learning activities are not only limited to being carried out face to face or face to face, especially during a pandemic which requires physical action, but learning activities can also be carried out remotely either directly at the same time which is often referred to as virtual face to face. or through assignments by utilizing an internet and technology-based learning platform. Differences in location between teachers and students are no longer an obstacle because they can still connect with each other using an interactive communication system. Through information and communication technology developing as it is today, teachers and students have the choice to carry out learning activities in real time (one at a time) or within a certain period of time which can be done through learning platforms, two of which are Google Forms and quizzes. This research uses a literature study method which includes literature search, selection, evaluation, analysis, summary, as well as synthesis and retrieval of information from various relevant sources. The results show that e-Evaluation in learning is an alternative that can be used to measure student learning outcomes in the application of distance learning. This also allows teachers and students to adapt to developments in science and technology